Right in the context of philosophical and legal thinking - Подковенко, Тетяна Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The article examines current approaches to understanding the nature and purpose of law in society. Therole of philosophy of law in comprehending the phenomenon of law in the light of modern concepts ofcomprehension.